Identifying strategies for dealing with the aging population from the perspective of health system experts: A qualitative study - Rahele Samouei; Mahmoud Keyvanara (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND AND AIM: Given the growing trend of aging and the limited resources of the health system, the lack of long-term prior government planning, and reduced growth of the productive force of society, identifying strategies for planning and action to deal with future aging is very important. In this regard, the study was conducted to identify strategies for dealing with the aging population from the perspective of health system experts. METHODS: The qualitative content analysis study was performed on 29 Iranian male and female experts in the aging and health scope from Isfahan, Tehran, Tabriz, and Babol who purposefully participated in the semi-structured interview. Data were classified by qualitative content analysis. RESULTS: Two concepts emerged according to the participated experts' opinions, regarding the strategies of the Iranian health system in dealing with future aging: "executive policy" strategies, including "design, planning and implementation," "evaluation and standardization," "strengthening demand-driven" and "modeling national and international experiences," "preventive policies" strategy, which includes "Focus on prevention," "Focus on values and competencies," "Educational empowerment," "Knowledge-based empowerment," "Empowerment of age-related groups," "Economic empowerment," and "Social support." CONCLUSION: The diversity and breadth of the mentioned strategies indicate the necessity of comprehensive readiness and adaptation of health services to the elderly conditions and characteristics. Purposeful planning and timely implementation of programs and policies to better address the health system with future aging will be possible by using practical strategies.